Attitudinal Analysis of Ideology Inside Barack Obama’s Inaugural Speech - Suswanto Ismadi Megah (Universitas Veteran Bangun Nusantara, 2020)
This study explores ideology inside president Barack Obama’s inaugiral speech. This paper used descriptive – qualitative method to find ideology through attitudinal analysis of Martina and white (2005). The data was obtained from the transcription of Barack Obama’s inaugural speech as the data. The findings are thirty effect, thirty-o judgments, and six appreciations. The analysis of data consists of the positive and negative attitude of study reveal that three sub-systems of language appraisal namely are (a). Affect found 30 data (44,7%) consist of positive 18 data, negative 12 data, (b). Judgment found 33 data (47,2%) consist of positive 31 data, negative 2 data, (c). Appreciation found 6 data (9,1%) consist of positive 6 data, negative 0 data and also the researcher found that President Barack Obama uses more Positive Judgmental category most frequently used by Obama and some of Barack Obama's statements which indicate he has views or ideologies such as 1) protectionism and 2) anti-racism. The ideological stance inside the speech of Obama is to maintain a close relationship with the public and protection of American people in order to get people’s sympathy.Keywords: Attitudinal analysis, Ideology, Inaugural Speech, and President Obama